Analisis Kinerja Keuangan Daerah Serta Pengaruhnya terhadap Belanja Modal Kabupaten Batang Hari - Edison Edison; Esti Susilawati; Yorina An’guna Bansa (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This research entitled "Analysis local financial performance Its Influence To Capital Expenditure Of Regency Of Batang Hari ". The purpose of the study is 1). To know and DOF, RKD And RKKD of the districts of Batang Hari region; 2). To know and analyze the influence of DOF, RKD And RKKD on capital expenditure The districts of Batang Hari. This research uses descriptive quantitative analysis method. Descriptive analysis to analyze local financial capacity and quantitative analysis to analyze the influence of local financial ability on capital expenditure. The result of analysis shows that the financial capacity of Batang Hari Regency is seen from the degree of fiscal autonomy and the ratio of regional financial independence is categorized very low as well as the regional financial dependency ratio is still very high. The degree of fiscal autonomy have significant effect on the capital spending of the local government of Batang Hari Regency, then the ratio of local financial independence and of regional financial dependency have no significant effect on the capital spending of the local government of Batang Hari Regency..